A comparative study of computed Tomographic Angiography and digital subtraction Angiography in evaluation of Aneurysmal Subarachnoid Haemorrhage - Islam, Mahmudul; Chowdhury, Ahmed Hossain; Chowdhury, Md Shah Jahirul Hoque; Islam, Md Nahidul; Nayeem, Abu; Khan, Sharifuddin; Rahman, Kazi Mohibur; Sarkar, Rabindranath; Mohammad, Quazi Deen (Journal of Dhaka Medical College, 2015)
Context: The aim of the study was to retrospectively analyze the performance of Computed Tomographic Angiography (CTA) in detecting, localizing and sizing intracranial aneurysms in patients of aneurysmal subarachnoid haemorrhage using Digital Subtraction Angiography (DSA) as standard. Methods: The study was carried out from December 2009 to November 2010 in the Dept. of Neurology of Dhaka Medical College Hospital, Dhaka. Among 81 patients of SAH admitted in the above mentioned period, 30 were enrolled in the study as they met the inclusion criteria. Patients age range was 26 to 70 years; male female ratio was 1.5: 1. All the study patients underwent both DSA and CTA examinations. The findings of both procedures were recorded and compared. Results: A total of 30 aneurysms in 30 patients were identified on DSA. Among 10 small sized aneurysms (<4 mm) detected by DSA, CTA incorrectly diagnosed 2 and overlooked 2 aneurysms. Out of 14 medium sized (5- 12 mm) identified on DSA, CTA missed 2 aneurysms. But CTA correctly diagnosed all 6 large (e13 mm) aneurysms. The overall sensitivity of CTA was 60% for small, 85.7% for medium and 100% for large aneurysm. Regarding identification of aneurysmal sites, CTA correctly localized 22 (73.4%), incorrectly localized 4 (13.3%) and missed 4 (13.3%) cases. Sensitivity of CTA in identification of aneurysmal site was 73.3%. Conclusion: CTA is less sensitive than DSA in detecting small and medium sized aneurysms. However it correlated perfectly with DSA in detection of large aneurysms. The performance of CTA in identification of aneurysmal site is also lesser than DSA. So, DSA remains the standard technique for evaluation of aneurysmal SAH. DOI: http://dx.doi.org/10.3329/jdmc.v22i2.21542 J Dhaka Medical College, Vol. 22, No.2, October, 2013, Page 195-200